Report. - Protestant Episcopal Church in the Philippines (Missionary District). (Manila [s.n.], 1901)
Annual.
"The Missionary District of the Philippine Islands was established in 1901. Owing to the fact that no meeting of Convocation was held in the years 1902, 1905, 1919, 1920, 1923, 1925, 1926, 1932 and 1935; and no report was published for the years 1902, 1904, 1921, 1923, 1924, 1925, 1931 and 1934" - inside front cover 29th annual report, 1937.